Letter to the Editor - Dyson, M (Sweet and Maxwell, 2016)
Sir Richard Buxton is right that Jogee; Ruddock [2016] UKSC 8; [2016] UKPC 7; [2016] 2 W.L.R. 681 (henceforth, Jogee) has changed the law of complicity significantly (“Jogee: upheaval in secondary liability for murder” [2016] Crim LR 324). Parasitic complicity is history. It was removed by expunging the first unambiguous statement of principle in support of such a form of liability, found in Chan Wing-Siu. 2 What needs careful unpacking is what the law was changed from, what it has been changed to, and whether the change will be significant. Some limited points in response to Sir Richard may assist in this ongoing endeavour, particularly in respect of the fault requirements for complicity.